مساهمة المنصات الرقمية في دعم الإبتكار البيداغوجي في الجامعة جامعة محمد الشريف مساعدية أنموذجا - حداد درصاف; غرايبية حياة (My University, 2025)
Summary Through this study, we aim to determine the extent to which digital platforms contribute to supporting pedagogical innovation at Mohamed-Chérif Messaadia University in Souk Ahras, by focusing on the effectiveness of digital platforms in developing flexible learning skills and improving the quality of educational outcomes. Based on a set of methodological procedures appropriate to the descriptive research type, the survey method was chosen, as it falls under descriptive research and relies on several methodological steps that align with the objectives of our study. The fieldwork was conducted from April 11 to May 10 at Mohamed-Chérif Messaadia University in Souk Ahras, Algeria. The research community consisted of the university’s human staff, including professors and students. As for the sample, the available sample was used. Regarding data collection tools, we used an electronic questionnaire directed to both students and professors at Mohamed-Chérif Messaadia University in Souk Ahras. The main results obtained are as follows: - Digital platforms are used only partially within the university, with irregular use and limited reliance on individual initiatives. - They have contributed to enhancing self-directed and flexible learning by fostering autonomy, improving time management, and providing easy access to educational resources. - There is a variation in the level of digital interaction, reflecting differences in digital readiness and engagement in the digital learning environment. - The lack of training is one of the key factors that weakens the effectiveness of pedagogical innovation, due to the absence of structured guidance and dedicated training programs. - The university faces both technical and pedagogical challenges, notably weak infrastructure, lack of support, and the absence of adequate digital instructional design. - Despite growing awareness of the importance of digitization, the absence of institutional activation and integrated strategies limits the actual transition to digital education. ------------------------------------------ الملخص نهدف من خلال هذه الدراسة لمعرفة مدى مساهمة المنصات الرقمية في دعم الابتكار البيداغوجي بجامعة محمد الشريف مساعدية سوق أهراس، وذلك بالتركيز على معرفة فعالية المنصات الرقمية في تطوير كل من مهارات التعلم المرن، وتحسين جودة المخرجات التعليمية. بالإعتماد على مجموعة الإجراءات المنهجية وفق نوع البحث الوصفي تم اختيار المنهج المسحي الذي يندرج ضمن البحوث الوصفية والذي يعتمد على العديد من الإجراءات المنهجية التي تتناسب مع أهداف دراستنا، إستغرق البحث في الجانب الميداني فترة زمنية حددت من 11 أفريل إلى10 ماي بجامعة محمد الشريف مساعدية لولاية سوق أهراس بالجزائر، تمثل مجتمع البحث في الطاقم البشري للجامعة من أساتذة وطلبة، أما بالنسبة للعينة، فقد تم الاعتماد على العينة المتاحة. فيما يخص أدوات جمع البيانات فقد استخدمنا: الاستبيان الإلكتروني موجه لكل من للطلبة وللأساتذة بجامعة محمد الشريف مساعدية سوق أهراس. وقد توصلنا إلى جملة من النتائج أهمها: - تستخدم المنصات الرقمية داخل الجامعة بشكل جزئي، في ظل غياب التوظيف المنتظم واعتماد محدود على المبادرات الفردية. - ساهمت المنصات الرقمية في تعزيز التعلم الذاتي والمرن من خلال تنمية الاستقلالية وتحسين إدارة الوقت وتوفير الوصول السهل إلى الموارد التعليمية. - يشهد التعليم الرقمي تفاوتا في مستويات التفاعل، مما يعكس اختلافا في الاستعداد الرقمي والانخراط في البيئة التعليمية الرقمية. - يعد غياب التكوين من أبرز العوامل التي تضعف فعالية الابتكار البيداغوجي، نتيجة نقص التأطير وغياب برامج تدريبية موجهة. - تواجه الجامعة تحديات تقنية وبيداغوجية، أبرزها ضعف البنية التحتية، نقص الدعم، وغياب التصميم التربوي الرقمي الملائم. - رغم الوعي المتزايد بأهمية الرقمنة إلا أن غياب التفعيل المؤسساتي والاستراتيجيات المتكاملة يحدّ من الانتقال الفعلي نحو التعليم الرقمي. ----------------------------------- Résumé À travers cette étude, nous visons à déterminer dans quelle mesure les plateformes numériques contribuent au soutien de l’innovation pédagogique à l’Université Mohamed Chérif Messaadia de Souk Ahras, en mettant l’accent sur l’efficacité des plateformes numériques dans le développement des compétences d’apprentissage flexible et l’amélioration de la qualité des résultats pédagogiques. La recherche sur le terrain a été menée du 11 avril au 10 mai à l’Université Mohamed Chérif Messaadia de Souk Ahras, en Algérie. La population de recherche était composée du personnel humain de l’université, incluant les enseignants et les étudiants. En ce qui concerne l’échantillon, nous avons utilisé l’échantillon disponible. Pour les outils de collecte de données, nous avons utilisé un questionnaire électronique destiné à la fois aux étudiants et aux enseignants de l’Université Mohamed Chérif Messaadia de Souk Ahras. Les principaux résultats obtenus sont les suivants : - Les plateformes numériques sont utilisées de manière partielle et irrégulière, avec un recours limité à des initiatives individuelles. - Elles ont contribué au développement de l’apprentissage autonome et flexible en favorisant l’autonomie, l’amélioration de la gestion du temps et l’accès facile aux ressources pédagogiques. - Il existe une variation dans le niveau d’interaction numérique, reflétant des différences dans la préparation numérique et l’engagement dans l’environnement d’apprentissage numérique. - L’absence de formation est l’un des facteurs clés qui affaiblit l’efficacité de l’innovation pédagogique, en raison du manque d’encadrement et de l’absence de programmes de formation dédiés. - L’université fait face à des défis à la fois techniques et pédagogiques, notamment la faiblesse de l’infrastructure, le manque de soutien, et l’absence de conception pédagogique numérique adéquate. - Malgré une prise de conscience croissante de l’importance de la numérisation, l’absence de mise en œuvre institutionnelle et de stratégies intégrées limite le passage effectif vers l’enseignement numérique.
Keywords: الابتكار البيداغوجي، المنصات الرقمية، التعليم العالي، جامعة محمد الشريف مساعدية، تكنولوجيا التعليم، التعليم الإلكتروني، التحول الرقمي